The impact of exercise self-efficacy on depression in firefighters: mediating effect of basic psychological needs and moderating effect of perceived social support - Chen, Wenjia; Yao, Jiayi; Zhu, Guoqing; Liu, Zongyu; Wang, Haozhe; Chu, Dengshan; Niu, Haitao (Frontiers in Psychology, 2025)
BackgroundFirefighters are exposed to high-stress work environments and are prone to depression, which has a significant impact on their professional performance and quality of life. Although exercise self-efficacy has been suggested to potentially influence psychological wellbeing, its mechanism of action on firefighters' depression has not been clarified.MethodsThis study investigated the relationship between exercise self-efficacy and depression in firefighters and examined the mediating role of basic psychological needs and the moderating role of perceived social support. A cross-sectional research design was used to survey 450 Chinese frontline firefighters (mean age = 24.03 ± 5.27 years). Data were collected using the Exercise Self-Efficacy Scale (SES), the General Scale of Satisfaction with Basic Needs (BNSG-S), Patient Health Questionnaire-9 (PHQ-9), and Perceived Social Support Scale (PSSS). Descriptive statistics, correlation analyses, and moderated mediated effects analyses were performed using SPSS 22.0 and Hayes' PROCESS macro.ResultsExercise self-efficacy significantly and negatively predicted depression levels after controlling for demographic variables (β = −0.249, p < 0.01). Basic psychological needs partially mediated the association between exercise self-efficacy and depression (indirect effect β = −0.131, 95% CI: [−0.174, −0.096]), accounting for 52.61% of the total effect. Perceived social support moderated the direct association between exercise self-efficacy and depression, which was stronger at high levels of perceived social support (β = −0.234, 95% CI: [−0.365, −0.104], p < 0.001).ConclusionsThis study reveals the mechanisms by which exercise self-efficacy influences firefighter depression levels through direct and indirect pathways, highlighting the critical role of basic psychological needs and perceived social support. These findings provide a theoretical basis for the development of targeted mental health intervention strategies for firefighters, emphasizing the importance of improving exercise self-efficacy, meeting basic psychological needs, and enhancing social support.